PEMBELAJARAN MATERI VOLUME PRISMA SEGITIGA DAN TABUNG MENGGUNAKAN MODEL PEMBELAJARAN STAD KELAS VI SD - Triyanti, Irma (Jurnal Kajian Pembelajaran dan Keilmuan, 2018)
Abstract: The lack of knowledge about how to imply mathematics in daily life, the lack of students’ readiness to follow mathematics lesson, and the lack of the teacher’s mathematical ability became  the obstacles in learning mathematics. The purposes of this paper were to describe the conditions of SDN 22 Seladu and Mathematics learning scenarios in class VI SDN 22 Seladu by applying STAD learning model, with steps as follows; (1) The teacher formed groups, 4 members were heterogeneous; (2) The teacher presented the lessons; (3) The teacher assigned the task to the groups to be done by members of the groups. (4) The students that could answer the questions, explained to other group members, so that all members in the group understood ; (5) The teacher gave the quiz to all students. At the time of answering the quiz, they  were not allowed to help each other. (6) The teacher rewarded  the group with points; (7) The teacher gave the evaluation; (8) closing. It was concluded that the application  of STAD cooperative learning model could make students active in learning.Keywords: STAD Learning Model, Material of Triangle Prism Volume  and Tube